2023
DOI: 10.3389/fimmu.2023.1132983
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral microbiota on pathophysiology of GVHD

Abstract: Allogeneic transplantation of hematopoietic cells is the only curative therapy for several hematopoietic disease in which patients receive cytotoxic conditioning regimens followed by infusion of hematopoietic stem cells. Although the outcomes have improved over the past decades, graft-versus-host-disease (GVHD), the most common life-threatening complication, remains a major cause of non-relapse morbidity and mortality. Pathophysiology of acute GVHD characterized by host antigen-presenting cells after tissue da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…Prolonged salivary gland cGVHD is associated with increased albumin, sodium, and anti-microbial proteins, such as lactoferrin ( 47 , 72 , 119 , 127 ). It is noteworthy to recognize that the interaction of and changes to the microbiota in oral cGVHD remains under explored and an area for potential future research ( 128 , 129 ).…”
Section: Gvhd Pathophysiology and Biological Phasesmentioning
confidence: 99%
“…Prolonged salivary gland cGVHD is associated with increased albumin, sodium, and anti-microbial proteins, such as lactoferrin ( 47 , 72 , 119 , 127 ). It is noteworthy to recognize that the interaction of and changes to the microbiota in oral cGVHD remains under explored and an area for potential future research ( 128 , 129 ).…”
Section: Gvhd Pathophysiology and Biological Phasesmentioning
confidence: 99%
“…An increasing number of studies have shown that chemotherapy, reduction of oral intake, and broad-spectrum antibiotics play important roles in the pathophysiology of GvHD through the loss of gut microbiota diversity and the domination of a single bacterial taxon. The composition of oral and gut microbiota influences GvHD occurrence and severity [17,18]. One study revealed the role of Actinomyces and Prevotella melaninogenica in the oral cavity and of Lactobacillus in the gut of children before the allo-HCT procedure in predicting severe (grade III-IV) GvHD.…”
Section: Key Pointsmentioning
confidence: 99%